2018
DOI: 10.1002/lt.25291
|View full text |Cite
|
Sign up to set email alerts
|

Development of Clinical Criteria for Functional Assessment to Predict Primary Nonfunction of High‐Risk Livers Using Normothermic Machine Perfusion

Abstract: Increased use of high‐risk allografts is critical to meet the demand for liver transplantation. We aimed to identify criteria predicting viability of organs, currently declined for clinical transplantation, using functional assessment during normothermic machine perfusion (NMP). Twelve discarded human livers were subjected to NMP following static cold storage. Livers were perfused with a packed red cell–based fluid at 37°C for 6 hours. Multilevel statistical models for repeated measures were employed to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(127 citation statements)
references
References 30 publications
3
124
0
Order By: Relevance
“…Often livers, declined for transplantation on subjective assessment by the transplant surgeon, were shown to display minimal morphological changes after histological examination . We set out to evaluate the histological observations described earlier and correlate these data with relative miRNA levels and the HDmiR122/CDmiR222 ratio. Suzuki injury scores at the start and end of NMP were compared with our early predictors HDmiR‐122, CDmiR‐222, and their ratio in perfusate at 30 minutes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Often livers, declined for transplantation on subjective assessment by the transplant surgeon, were shown to display minimal morphological changes after histological examination . We set out to evaluate the histological observations described earlier and correlate these data with relative miRNA levels and the HDmiR122/CDmiR222 ratio. Suzuki injury scores at the start and end of NMP were compared with our early predictors HDmiR‐122, CDmiR‐222, and their ratio in perfusate at 30 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…Mergental et al proposed composite viability criteria based on analysis of 12 discarded human livers. Multilevel statistical analysis showed that lactate clearance stratified his cohort in 2 distinct groups with pH and bile production as discriminative parameters . It should, however, be noted that in studies where livers were transplanted after NMP, these parameters tend to vary extensively and are not predictive for transplant outcome after NMP alone .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations